Ethnicity and the surgical management of early invasive breast cancer in over 164 000 women. Issue 5 (26th May 2021) - Gathani, T; Chiuri, K; Broggio, J; Reeves, G; Barnes, I
Abstract: Background: Limited information is available about patterns of surgical management of early breast cancer by ethnicity of women in England, and any potential inequalities in the treatment received for breast cancer. Methods: National Cancer Registration and Analysis Service data for women diagnosed with early invasive breast cancer (ICD–10 C50) during 2012–2017 were analysed. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95 per cent confidence intervals for the risk of mastectomy versus breast‐conserving surgery by ethnicity (black African, black Caribbean, Indian, Pakistani and white), adjusting for age, region, deprivation, year of diagnosis, co‐morbidity and stage at diagnosis. Results: Data from 164 143 women were included in the analysis. The proportion of women undergoing mastectomy fell by approximately 5 per cent between 2012 and 2017 across all the ethnic groups examined. In unadjusted analyses, each ethnic minority group had a significantly higher odds of mastectomy than white women; however, in the fully adjusted model, there were no significantly increased odds of having mastectomy for women of any ethnic minority group examined. For example, compared with white women, the unadjusted and fully adjusted ORs for mastectomy were 1·14 (95 per cent c.i. 1·05 to 1·20) and 1·04 (0·96 to 1·14) respectively for Indian women, and 1·45 (1·30 to 1·62) and 1·00 (0·89 to 1·13) for black African women. This attenuation in OR by ethnicity was largely due to adjustment for age and stage. Conclusion: Allowing for different patterns of age and stage at presentation, the surgical management of early breast cancer is similar in all women, regardless of ethnicity.